Reliability of the dynamic balance test with a mobile application of the Physics Toolbox Suite - Atalay, E.; Kizildogan, E. T. (Journal of Sports Science & Medicine, 2025)
Although mobile applications are used as an alternative to expensive and difficult to access systems used to evaluate dynamic balance, existing applications have some shortcomings. This study aimed to evaluate the reliability of the Physics Toolbox Suite mobile application, which can obtain objective data for dynamic balance measurements in healthy adults, shorten the duration of measurements, and minimize the number of measurement equipment. The dynamic balance of 22 university students (9 male, 13 female, aged 20.3 (± 1.13 years)) was evaluated using the Physics Toolbox Suite mobile application in three test sessions with a 1-week interval. Anterior-posterior stability index (APSI), medial-lateral stability index (MLS), and overall stability index (OSI) of dynamic balance were calculated. Interclass Correlation Coefficients (ICC), Minimal Detectable Change (MDC), Standard Error of Measurement (SEM), and Coefficient of Variation for SEM (CVSEM) were evaluated as indicators of intra- and inter-rater reliability. The mean APSI, MLSI, and OSI scores (Standard deviation) were 2.59 (0.69), 2.21 (0.68), and 3.58 (0.94), respectively. In the evaluation made with the Physics Toolbox Suite mobile application, APSI scores had good intra-rater (ICC(3,1) = 0.67) and inter-rater reliability (ICC(3,1) = 0.73), MLSI scores had high intra-rater (ICC(3,1) = 0.90) with good inter-rater reliability (ICC(3,1) = 0.71), and OSI scores had high intra- rater (ICC(3,1) = 0.87) with good inter-rater reliability (ICC(3,1) = 0.73). The Physics Toolbox Suite Mobile Application can be used as a reliable objective tool to assess dynamic balance among healthcare professionals and athletes.